Penyempitan Makna Amelioratif pada Nomina dalam Bahasa Inggris - Erlan Aditya Ardiansyah (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2020)
Semantic change is a language phenomenon which may be found in a society. A kind of semantic change which which is remarkable to be examined is semantic narrowing. A positive meaning namely amelioration may be discovered through semantic narrowing. In addition, semantic narrowing in English is frequently discovered i nouns. Therefore, factors which can stimulate the process are necessary to be elaborated. Aim of the study was to examine nouns’ ameliorative semantic narrowing in English. Methods applied in the study were descriptive synchronic-diachronic methods. The methods were used to describe portrayal relating to the condition in past and present. Data in the study were six nouns which were collected from the video clips relayed on the television programs. Semantic narrowing found in the study were caused by several factors: (a), meaning change due to environmental change (b) meaning change due to language users’ response, and (c) meaning change due to association. The results showed that semantic narrowing has a correlation with homonymy and polysemy. Therefore, meaning change may have related or non-related meaning from the previous meaning. Longer period of the process and the society agreement have become challanges which should be realized due to acceptance of the new meaning.